Determinants of the weight for leisure in preferences - Ceyhun Elgin; Emekcan Yucel (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
In this paper, the authors investigate the determinants of weight for leisure in preferences. First, using a dynamic general equilibrium model, they back out the weight for leisure for an unbalanced panel of 52 countries over the period from 1950 to 2009. Then, the authors perform several panel data regressions using the backed-out values of the preference for leisure as the dependent variable. Estimation results imply that trade openness, GDP per-capita and average temperature positively affect the weight for leisure in preferences in a robust manner. They also find some evidence about the effect of unionization and unemployment.
Keywords: C23; C33; J20; J22; 330; Leisure; preferences; panel data